STRATEGI BURUH PETANI SAWIT DALAM MEMENUHI KEHIDUPAN KELUARGA (STUDI PTPN III SEI MERANTI DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR) - Sandi Asriadi Khaz; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The plantation sector is one of the most strategic agricultural sectors to be developed. For Indonesia, oil palm crops have important significance for the development of national plantations because they are able to create employment opportunities that lead to the welfare of the people and as a source of state foreign exchange earnings. The author is interested in researching farm workers as harvests in PTPN III Sei Meranti in Kecamatan Bagan Sinembah because the majority of farm workers in Kecamatan Bagan sinembah are still categorized in the middle to lower class and many also among the farm workers to meet the needs of their family is still less than the producer. The formulation of the problem (1) How socio-economic conditions of oil palm farmers (2) How the farm labor strategy in meeting family needs. (3) What is the reason and socio-economic background of farm laborers in choosing family fulfillment strategy. The purpose of this study is to describe the socio-economic conditions of oil palm farmers, to find out the farm labor strategies in meeting family needs, and to find out the reasons and socio-economic background of farm workers in choosing family fulfillment strategies. The theory used is a survival strategy. The research method used is descriptive quantitative. The location of this research in PTPN III Sei Meranti in Kecamatan Bagan Sinembah Rokan Hilir Regency. The population in this study amounted to 326 people. Samples taken amounted to 65 people. Data analysis techniques used descriptive quantitative percentage. The result of this research is seen from socio-economic characteristic of family of palm oil farmer of PTPN III Sei Meranti that is majority of education graduate of elementary and junior high school, while in view from amount of family income equal to Rp. 1,500,000-Rp. 3,000,000. The strategy of fulfilling the needs of the family of the farming workers that have been employed are among others: (a) Active Strategy by the family of the palm oil workers is the role of the members of the family. (b) A passive strategy is a survival strategy by applying a frugal pattern. (c) Network Strategy by the families of oil palm farmers generally borrows money to BANK, families and cooperatives.Keywords: Strategy, Palm Farmer, Fulfilling Family Life.